Spreading profile of dopant solution on pre-sintered silica layers for selective area doping of integrated optic planar glass samples - Leong, W.C.; Tho, S.Y.; Law, A.W.P.; Chong, W.Y.; Pua, C.H.; Ahmad, Harith; Haseeb, A.S. Md. Abdul; Adikan, Faisal Rafiq Mahamd (Elsevier, 2009)
The spread profile of potassium-permanganate (KMnO(4)) dye on a porous pre-sintered silica layer deposited via Flame Hydrolysis Deposition is presented. The work is aimed at controlling the dopant profile on the resulting glass layer for optically passive and active devices integration. KMnO(4) is used as it allows visual qualification of its spread on the soot layer. Pre-sintered silica layers allow for application of dopants into the glass matrix via adsorption and pore retention. Selective area doping is achieved by applying specific volumes of the dye onto pre-selected areas on the sample using a micropipette. Higher dye volumes applied would result in larger spread diameters. Furthermore, control of the spread is possible by heating the sample during the application of the dye. (C) 2009 Elsevier B.V. All rights reserved.